The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/1758-2229.12794
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, diversity and plant‐specific adaptations of plant‐associated lactic acid bacteria

Abstract: Summary Lactic acid bacteria (LAB) are essential for many fruit, vegetable and grain food and beverage fermentations. However, the numbers, diversity and plant‐specific adaptions of LAB found on plant tissues prior to the start of those fermentations are not well understood. When measured, these bacteria have been recovered from the aerial surfaces of plants in a range from <10 CFU g−1 to over 108.5 CFU g−1 of plant tissue and in lower quantities from the soil and rhizosphere. Plant‐associated LAB include well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 137 publications
2
54
0
Order By: Relevance
“…These findings were corroborated by comprehensive genomic comparisons of L. lactis isolates that revealed lactococci adapted for use in dairy fermentations exhibited a loss of functions likely necessary for survival in plant environments [22]. Moreover, recent studies demonstrated that strains of L. lactis are found in numerous plants as integral members of the microbiome and are likely to exhibit distinct genomes with uncharacterized metabolic capabilities [23][24][25][26].…”
Section: Introductionmentioning
confidence: 75%
“…These findings were corroborated by comprehensive genomic comparisons of L. lactis isolates that revealed lactococci adapted for use in dairy fermentations exhibited a loss of functions likely necessary for survival in plant environments [22]. Moreover, recent studies demonstrated that strains of L. lactis are found in numerous plants as integral members of the microbiome and are likely to exhibit distinct genomes with uncharacterized metabolic capabilities [23][24][25][26].…”
Section: Introductionmentioning
confidence: 75%
“…Microorganisms naturally present on forage are responsible for silage fermentation, but can be affected by many factors and vary widely [ 34 ]. Only 4.00 log 10 cfu/g FM of LAB was present in the raw OG ( Table 1 ), which was inadequate for natural fermentation during ensiling [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, directed and controlled fermentations can also be driven in order to obtain valorized final products; in spite of the low predominance of LAB in plant autochthonous microbiota, they can also be key players in plant and plant-derived waste fermentations (Filannino et al, 2018). The reason behind this is the high adaptation of LAB to inhabit different plant niches of fruits and vegetables, which include flowers, grains, leaves, and/or grasses (Yu et al, 2020). In addition, Yu et al (2020) have reported the distinction between generalist-and specialist-LAB in plant ecosystems; the first ones occupy a wide range of habitats but with a variable degree of performance, whilst the specialists are present in a narrow range of habitats and they are highly adapted to them.…”
Section: Fermentation Processes Employing Labmentioning
confidence: 99%
“…The reason behind this is the high adaptation of LAB to inhabit different plant niches of fruits and vegetables, which include flowers, grains, leaves, and/or grasses (Yu et al, 2020). In addition, Yu et al (2020) have reported the distinction between generalist-and specialist-LAB in plant ecosystems; the first ones occupy a wide range of habitats but with a variable degree of performance, whilst the specialists are present in a narrow range of habitats and they are highly adapted to them. The generalist-LAB have genomes of bigger size than the specialized once since they harbor a wide enzymatic machinery; an example of the first case is Lactiplantibacillus plantarum, widely isolated from plant and animal sources, meanwhile Fructilactobacillus sanfranciscensis is mainly associated with cereal (sourdough) fermentations.…”
Section: Fermentation Processes Employing Labmentioning
confidence: 99%